Sex differences in young patients with acute myocardial infarction. Issue 3 (20th February 2013) - Egiziano, G.; Akhtari, S.; Pilote, L.; Daskalopoulou, S. S.; ,
Abstract Aims To identify sex differences in risk factors, presenting symptoms and outcomes of young patients with acute myocardial infarction. Methods We adopted a comprehensive approach and performed two parallel studies: (1) using provincial administrative databases from Quebec, Canada from 2000 to 2007, we identified baseline characteristics and post‐acute myocardial infarction survival of patients aged < 50 years (n = 10 619); (2) to overcome the lack of clinical data in the administrative databases, a medical chart review was performed on 215 patients < 50 years of age with an acute myocardial infarction between April 2000 and August 2006 from our institution. Results Administrative cohort: fewer women than men sought medical attention for retrosternal chest pain 1‐month pre‐acute myocardial infarction (P = 0.035). Diabetes and hypertension were more prevalent in women, and patients equally received interventional procedures post‐infarction. Diabetes significantly reduced post‐infarction survival in men and women [HR = 2.02 (95% CI 1.21–3.36) and HR = 2.25 (95% CI 1.06–4.80), respectively]. However, young women had greater post‐infarction mortality in‐hospital and up to 1 year after discharge (4.23% vs. 2.21%, respectively; P = 0.005). Medical chart review: diabetes and hypertension were more prevalent in women, while men were more obese. There were no significant sex differences in typical presenting symptoms, or in interventional procedures post‐infarction. Conclusions Young men and women with acute myocardial infarctions equally presented with retrosternal chest pain, although fewer women sought medical attention for retrosternal chest pain before admission. Diabetes and hypertension were more prevalent in young women, and mortality was higher in young female patients. Our results highlight the continued need for diabetes prevention and control in young patients, especially women.